Adubação nitrogenada e orgânica em videira: características químicas do solo, componentes produtivos e decomposição de resíduos foliares e esterco bovino - Lima, Franciezer Vicente de (2017)
The cultivation of the vine in the semi-arid region of the Northeast is a consecrated reality, for example the Sub-Valley of the São Francisco Valley, which currently accounts for a large part of the national grape production. The Potiguar Western region of presents conditions to explore this crop, however, there is little research on the behavior of the grapevine in soils of this region. Considering the low natural availability of organic matter (OM) and consequently nitrogen (N), as well as the use of organic sources to improve soil fertility and OM accumulation, the objective was to evaluate the effects of nitrogen and organic fertilization on the chemical characteristics of the soil and on the production components of 'Isabel Precoce' vine, as well as the dynamics of the decomposition of leaf litter and cattle manure when submitted to nitrogen fertilization in the semi-arid conditions of the Potiguar West region. Experiments were implemented at the UFERSA Farm in Mossoró, RN, consisting of four research fronts. In the Experiment I, the chemical characteristics of the soil were evaluated. The experimental design was a randomized complete block design in a 5 x 2 factorial scheme, corresponding to 5 doses of nitrogen fertilizer (0, 30, 60, 90 and 120 kg ha-1), with and without organic fertilization (AO) (0 and 20 m3 ha-1, of bovine manure), distributed in 6 blocks. Micronutrients (Na, Fe, Mn and Zn), as well as pH, electrical conductivity, organic matter and base sum were evaluated (N, P, K, Ca and Mg) and micronutrients. The interaction N and AO, caused increase in macro and micronutrient contents, in organic matter and in the sum of bases. N doses were responsible for reducing pH levels to a level that provided greater availability of nutrients. In the Experiment II, the same design of experiment I was followed. The number of bunches per plant, yield per plant and productivity, besides the weight, length and width of the bunches, number of berries per bunch and weight of ten berries were evaluated. The dose of 60 kg ha-1 of N in the presence of AO provided the best results for the production components analyzed. The elevation of N levels, from the dose of 60 to 120 kg ha-1 combined or not with the organic source, inhibited the productive components of the vine 'Isabel Precoce'. In the Experiment III, it was evaluated the decomposition of grape leaves and the nutrient release when submitted to nitrogen fertilization. A completely randomized design was used with 4 replications, in a 6 x 2 factorial scheme, 6 collection times (0, 20, 40, 60, 90 and 120 days), with and without addition of N (0 and 60 kg ha-1). The addition of 60 kg ha-1 of N in the vineyard residues, although reducing the C: N ratio, did not influence the rate of decomposition of residues left on the soil surface. Nitrogen fertilization promoted an increase in the release rate of P and Mg, decreasing its final release by 27 and 23 days. Experiment IV followed the same statistical design of experiment III, however, the decomposition and nutrient release of bovine manure was evaluated. Nitrogen fertilization in cattle manure, although reducing the C:N ratio, did not influence the decomposition rate of manure or carbon mineralization. The addition of nitrogen promoted greater release of P, Mg, K, reducing the time for 95% of the nutrients contained in the residues to be released in 27, 65 and 226 days